Cyclometalated Ruthenium Pincer Complexes as Catalysts for the α‐Alkylation of Ketones with Alcohols - Piehl, Patrick (Chemistry, 2020)
Ruthenium PNP pincer complexes bearing supplementary cyclometalated C,N‐bound ligands have been prepared and fully characterized for the first time. By replacing CO and H(−) as ancillary ligands in such complexes, additional electronic and steric modifications of this topical class of catalysts are possible. The advantages of the new catalysts are demonstrated in the general α‐alkylation of ketones with alcohols following a hydrogen autotransfer protocol. Herein, various aliphatic and benzylic alcohols were applied as green alkylating agents for ketones bearing aromatic, heteroaromatic or aliphatic substituents as well as cyclic ones. Mechanistic investigations revealed that during catalysis, Ru carboxylate complexes are predominantly formed whereas neither the PNP nor the CN ligand are released from the catalyst in significant amounts.